2014
DOI: 10.1007/s00701-014-2115-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumour and surgery effects on cognitive functioning in high-grade glioma patients

Abstract: Tumour-related cognitive deficits are present in a majority of HGG patients preceding surgery. Surgery does not result in cognitive deterioration in the short term in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
73
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 28 publications
9
73
2
3
Order By: Relevance
“…4 With regard to tumor laterality, patients with left-sided meningiomas had decreased verbal fluency and recall for verbal material compared with patients with right-sided meningiomas. This finding supports the well-established notion that the left hemisphere is dominant for language function 15 and is in agreement with previous studies reporting verbal deficits in patients with left-hemisphere benign, 28 low-grade, 9 and high-grade malignancy 12 tumors. Regarding the superoinferior axis, patients with skull base meningiomas had more deficits in memory components and long-term verbal and nonverbal memory than those with convexity meningiomas.…”
Section: Discussionsupporting
confidence: 93%
“…4 With regard to tumor laterality, patients with left-sided meningiomas had decreased verbal fluency and recall for verbal material compared with patients with right-sided meningiomas. This finding supports the well-established notion that the left hemisphere is dominant for language function 15 and is in agreement with previous studies reporting verbal deficits in patients with left-hemisphere benign, 28 low-grade, 9 and high-grade malignancy 12 tumors. Regarding the superoinferior axis, patients with skull base meningiomas had more deficits in memory components and long-term verbal and nonverbal memory than those with convexity meningiomas.…”
Section: Discussionsupporting
confidence: 93%
“…This group includes few patients and these data deserves further investigation. Nonetheless data are in line with other studies showing improvements at follow-up in information processing speed and visuo-construction [8]. In addition data evidence oscillatory evolution of patients' performance, with immediate post-surgery worsening and improvements at follow-up, in line with other studies showing a mild decline 12-month after surgery, and a mild improvement slightly at an additional follow-up (before the 18 th month) [9].…”
Section: Discussionsupporting
confidence: 90%
“…This hypothesis is indeed in line with clinical indications showing improvements at follow-up. For instance, Habets et al [8] found significant improvements in information processing speed and visuo-construction at follow-up. Similarly, Correa et al [9] studied twenty-five low-grade glioma patients pre-surgery and at 6 and 12 months and found a mild decline 12-month after surgery, and a mild improvement slightly at an additional follow-up (before the 18 th month).…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike the current study, in Habets et al's study (25), patients, who were unable to fully complete cognitive testing were clearly older and most of them were female (P = 0.009). There is significant evidence suggesting Rep Radiother Oncol.…”
Section: Discussioncontrasting
confidence: 80%
“…In addition, in the study of Habets et al (25), there was a significant correlation between age and cognitive function in patients after surgery.…”
Section: Discussionmentioning
confidence: 85%